2022
DOI: 10.3389/fpsyg.2022.813677
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Sequences of Learners' Self-Regulatory Interactions With Instructional Material During Game-Based Learning Using Auto-Recurrence Quantification Analysis

Abstract: Undergraduate students (N = 82) learned about microbiology with Crystal Island, a game-based learning environment (GBLE), which required participants to interact with instructional materials (i.e., books and research articles, non-player character [NPC] dialogue, posters) spread throughout the game. Participants were randomly assigned to one of two conditions: full agency, where they had complete control over their actions, and partial agency, where they were required to complete an ordered play-through of Cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…We have also used unsupervised machine learning techniques to examine ( Lallé et al, 2018 , 2021 ; Wortha et al, 2019 ; Wiedbusch and Azevedo, 2020 ) complex eye-tracking data and facial expressions of emotions during learning with MetaTutor. We continue to use non-traditional statistical techniques, including dynamical systems modeling ( Dever et al, in press ) to examine learners’ emergent SRL behaviors, and MLAs to predict performance at the end of the learning session ( Mu et al, 2020 ; Saint et al, 2020 ; Chango et al, 2021 ; Fan et al, 2021 ). Despite our ability to continuously adapt and use contemporary analytical techniques that emerge from the computational, engineering, psychological, statistical, and data sciences, we as a field are still faced with a major barrier that continues to impact the educational effectiveness of intelligent systems such as MetaTutor.…”
Section: Contributions To the Field Of Self-regulated Learning And In...mentioning
confidence: 99%
See 1 more Smart Citation
“…We have also used unsupervised machine learning techniques to examine ( Lallé et al, 2018 , 2021 ; Wortha et al, 2019 ; Wiedbusch and Azevedo, 2020 ) complex eye-tracking data and facial expressions of emotions during learning with MetaTutor. We continue to use non-traditional statistical techniques, including dynamical systems modeling ( Dever et al, in press ) to examine learners’ emergent SRL behaviors, and MLAs to predict performance at the end of the learning session ( Mu et al, 2020 ; Saint et al, 2020 ; Chango et al, 2021 ; Fan et al, 2021 ). Despite our ability to continuously adapt and use contemporary analytical techniques that emerge from the computational, engineering, psychological, statistical, and data sciences, we as a field are still faced with a major barrier that continues to impact the educational effectiveness of intelligent systems such as MetaTutor.…”
Section: Contributions To the Field Of Self-regulated Learning And In...mentioning
confidence: 99%
“…This study explored the relationship between students' average monitoring micro-process strategy frequencies and learning gains through a personcentered approach as students interacted with MetaTutor. Using hierarchical clustering, Dever et al (2021) found that clusters differing in metacognitive monitoring process usage had a significant difference in their learning gains where students who used a greater proportion of CEs and FOKs had greater learning gains than learners who used greater MPTG strategies. These aforementioned studies demonstrate differences of when students engage in metacognitive processes during learning with MetaTutor.…”
Section: When Do Students Engage In Metacognitive Processes?mentioning
confidence: 99%
“…Online games have grown immensely popular over the past few decades, both as recreation and for specific applications such as mental, physical, and cognitive training ( Sailer and Homner, 2020 ; Dever et al, 2022 ; Han et al, 2022 ; Aydin and Kuş, 2023 ). These games can promote relaxation by allowing participants to leave their regular duties, and experience fantastical environments ( Sailer and Homner, 2020 ; Maldonado-Murciano et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies investigating the assessment and prediction of student knowledge in game‐based learning focus on one student population with a fixed set of assessment questions that are designed for that population (eg, multiple choice questions administered after the game) (Dever et al, 2021, 2022; Henderson et al, 2020; Taub et al, 2017, Taub, Sawyer, Lester, et al, 2020). This approach assumes that the content that will be assessed will not change.…”
Section: Introductionmentioning
confidence: 99%